The Implementation of Religious and Moral Education at Kindergarten - Fithriyah Putri Perdana; Agustinus Ngadiman (JournEEL, 2019)
Religious and moral education from an early age so needs to be invested for the child, so that in the future they will have a strong and deep understanding of the norms and teachings of Islam. Age children early childhood and kindergarten (TK) is a time to play, so education is implemented particularly religious education should be designed properly by the teacher so that the education process into an active and fun activities. Kindergarten (TK) Darma Wanita Sekardangan, Sidoarjo is one of the educational institutions that provide education for early childhood, with one lesson material is a moral and religious education. Moral education is one of the materials is very important because in load values, morals and religion, so this will be a guide for students in later life. The research method used is descriptive qualitative research to describe in detail the subjects and issues to be studied. The findings in this study is the cultivation of religious values and morals for children Kindergarten revolves around the activities of daily life. In particular cultivation of religious values with laying the foundations of the faith, personality or character that is commendable and devotional practices, in accordance with the child's ability is implemented. As one of the early childhood education institutions, in conducting the study, have several models of delivery Edutainment, habituation and uswah hasanah as a reference implementation of teaching and learning.